Experimental Study and Effects of Process Parameters of LM24 Aluminium Alloy in Cold Chamber High Pressure Die Casting - Gulia, Vikas (My University, 2014)
Cold Chamber High Pressure Die Casting is a process by which a molten non-ferrous material is forced under high pressure into reusable tool steel moulds. These moulds called dies can be designed to produce intricate shapes with a high degree of accuracy and repeatability and surface finish with smooth or textured surfaces. High Pressure Die Casting is best suited for mass production runs and can produce the least expensive parts. A variety of materials are available for the High Pressure Die Casting process. The materials and process charts can be used to help determine which are best suited for a specific application. Experiments in industrial environment were conducted producing wire clamp using commercially treated LM24 alloy. The different process parameter were varied such as injection pressure, pouring temperature, coating type, cooling type to understand their effect on the final product. The objective of this study is to evaluate the main effects i.e. thermal characteristics (temperature of the molten metal), injection pressure of the molten metal, type of coating (Oil + graphite coating, Dycote + graphite coating, Dycote coating), and the type of cooling (air cooling, water cooling and oil cooling) on impact strength of material, density of the material, hardness of the material and the surface roughness of the material. In the experiments I used transformer oil for coating and cooling because of high heat dissipation energy. The methodology used to calculate the effect of various parameters will also be studied using parameterization approach in design of experiment is Taguchi approach. Taguchi’s approach provides a powerful and efficient method for designing products that operate consistently and optimally over a variety of conditions. This approach allows quality considerations to be included at an early stage of any new venture; in the design phase for a product, during routine maintenance or during installation of a manufacturing process. Analysis of Variance (ANOVA) was performed for all the responses and the effect of the factors was explained with the help of main effect plots. Micro structural analysis for all the trials was done. The major finding and conclusion of this research is that control of various parameter such as pouring temperature, injection pressure, coating type, cooling type enhances the quality of product and suggest the different combination of process parameter which helps the product to sustain in the market.
M.E. (Production Engineering)
Keywords: LM24,Die Casting,Pouring Temp,Coating,Cooling